Redes de cooperação no cluster de restaurantes de Santa Felicidade - Paiva, Thiago dos Santos (2007)
The cooperation networks consist in companies' connections to reach a common goal. In Curitiba, these networks are found within companies conglomerates. Due to a great personal interest and academic background, this study aims to to analyze the cooperation networks in the services sector - specifically in the Santa Felicidade restaurants. The research objective is to perform a diagnosis of the restaurants' relationship towards a shared objective. The problem to be analyzed is how a network structure and its management can affect the development of a cooperation network. This analysis is necessary, as market landmarks had changed, and the companies search for new ways of survival and growth. To reach the proposed goal, first we analyzed the management systems, cluster, cooperation networks, the network stages and development. Finally, an interview schedule was performed in the Santa Felicidade restaurants, to cross information between the theory and the practice in the network. These interviews were thoroughly described and the network typology and the current situation of the restaurants inside the Santa Felicidade Cluster were analyzed.